1993
DOI: 10.1161/01.cir.88.3.846
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of coronary heart disease death in men with low total and low-density lipoprotein cholesterol in the Russian Lipid Research Clinics Prevalence Follow-up Study.

Abstract: The results of disclose a sizeable subset of hypocholesterolemics in this population at increased risk of cardiac death associated with lifestyle characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 18 publications
2
32
1
2
Order By: Relevance
“…This also shows the correlation since diabetes mellitus is one of the major risk factors for CHD. Similar observations were also found in a number of studies (Al-Harbi, 2004;Shestov et al, 1993;Castelli et al, 1977).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This also shows the correlation since diabetes mellitus is one of the major risk factors for CHD. Similar observations were also found in a number of studies (Al-Harbi, 2004;Shestov et al, 1993;Castelli et al, 1977).…”
Section: Discussionsupporting
confidence: 88%
“…This is different from the current study that may be due to dyslipidaemia which occasionally causes the development of CHD than other risk factor for example hypertension. Multiple Malaysian research revealed that HDL values were significantly higher in females than males and much lower among the Indian males, rather than Chinese and Malay (Ng et al, 1997;Tan et al, 2011;Blebil et al, 2011). In this study, male accounts for most of the samples that might have affected the result.…”
Section: Discussionmentioning
confidence: 59%
“…15,16 However, it appears that after the abolition of the State alcohol monopoly in 1992, the Russian populace has become one of the world leaders in alcohol consumption. 14,[17][18][19][20] As alcohol consumption could be a decisive factor, both directly and indirectly, for the high mortality rate in Russia, this study was designed to more carefully evaluate this role.…”
mentioning
confidence: 99%
“…A positive association of low TC levels with risk of death from coronary heart disease has earlier been reported in a Russian cohort study undertaken in 1980s (26). Hence, one may conclude that same forces increasing cardiovascular mortality are still present and influent in the Russian population in our days.…”
Section: Serum Lipids and Mortalitymentioning
confidence: 51%